(untitled) (Fiep Bulletin - online, 2014)
This research aimed to investigate the effects of an eight-week program of strength training on resting blood pressure levels in the elderly under non-pharmacological treatment. Took part in the survey, elderly aged over 60 years. The sample consisted of 21 elderly women with a mean age of 62.8 years. The research was a cross-sectional quantitative approach, field procedure and pre-experimental feature. Data were analyzed by BioEst, version 5.0. Statistical procedures corresponded to the paired t test to analyze differences between pre-and post-tests to the same sample. We also used the delta percentage (?%) to determine the percentage differences of the variables in relation to pre-and post-test. The results showed statistically significant data at a significance level of p ? 0.05, indicating that the training for the group in question contributed significantly to the reduction of blood pressure, and also using the delta method both arterial systolic pressure and diastolic blood Pressure decreased their average values ??over the pre-test, which is an important behavior for increased cardiac output and blood pressure control. From the data presented, we suggest the need for further studies involving exercises power using different methodologies and larger sample groups because, although the strength training is recommended for elderly and there are some hints that he may have chronic hypotensive effect, no parallel disputes on this subject, which shows that this is still an open field to research.